2007
DOI: 10.1007/s10346-007-0081-4
|View full text |Cite
|
Sign up to set email alerts
|

Ground reinforced embankments for rockfall protection: design and evaluation of full scale tests

Abstract: Infrastructures such as roads and railways as well as urbanised areas, in mountainside regions, can frequently be endangered by rockfalls and, therefore, need to be protected against the impact of rolling blocks. Among the various protection works that can be used, ground reinforced embankments can be considered a feasible technique. A set of full-scale tests on embankments made of ground reinforced by geogrids are presented and discussed. The experiments were performed in a specifically designed and construct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
58
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(61 citation statements)
references
References 20 publications
1
58
0
2
Order By: Relevance
“…For impact energies around 1000 kJ, the maximum deformation measured on structures tested by Maegawa et al (2011) was three times greater than that for cellular walls (our study). For impacts involving 2000 kJ kinetic energy projectiles, the latter type of structure performed similarly to structures tested by Peila et al (2000Peila et al ( , 2007 in terms of penetration.…”
Section: Comparison With Other Structure Typesmentioning
confidence: 60%
See 2 more Smart Citations
“…For impact energies around 1000 kJ, the maximum deformation measured on structures tested by Maegawa et al (2011) was three times greater than that for cellular walls (our study). For impacts involving 2000 kJ kinetic energy projectiles, the latter type of structure performed similarly to structures tested by Peila et al (2000Peila et al ( , 2007 in terms of penetration.…”
Section: Comparison With Other Structure Typesmentioning
confidence: 60%
“…Despite this variability, these experiments globally provide a valuable database for comparison with the results presented in this paper. For this purpose, a representative panel of experiments from Hearn et al (1996), Yoshida (1999), Peila et al (2000Peila et al ( , 2007, Sung et al (2008) Peila et al (2000Peila et al ( , 2007 4.2 0.9/5 2500 600 Burroughs et al (1993) 3.1 1.8/1.8 1400 900 Maegawa et al (2011) 4.2 2.2/4.3 2037 1730…”
Section: Comparison With Other Structure Typesmentioning
confidence: 99%
See 1 more Smart Citation
“…The maximum impact force (F m ) is, therefore, crucial during designing the protection measures. In the literature, the F m has been found to be affected by factors, such as platform on the slope, physical and mechanical properties of falling materials, and incident angle when collision happens (Jean and Pascal, 2005;Azzoni et al, 1995;Tetsuya, 2004;Peila et al, 2007). Jean and Pascal (2005) carried out experiments and indicated that the drop height is the most important factor influencing the F m .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore for a rockfall protection design to be successful it is necessary first to define the area of risk located below the unstable rock slope (Evans and Hungr, 1993;Crosta and Agliardi, 2003;Guzzetti et al, 2003;Locatelli, 2005) and to forecast of the possible trajectories of the falling blocks (Giani, 1992) and secondly to chose and design the correct method that can: stabilize the unstable rock block directly on the slopes (Peckover and Kerr, 1977;Giani, 1992, Duncan andNorman, 1996;Oggeri and Peila, 2000), stop an already moving block or blocks through technological devices mainly located at the bottom of the slope (Peila et al, 1998(Peila et al, , 2006(Peila et al, , 2007Pelizza et al, 2004), or conduct operations to remove the unstable elements (Cardu et al, 2004;DeWall, 1996;Goumans and Wallace, 1999;Philippon, 2001;Woolf and Goumans, 2002;Mackenzie, 2004).…”
Section: Introductionmentioning
confidence: 99%